Physiological and Haematological Stress Responses of Labeo catla Fingerlings in Relation to Stocking Density during Pre-transport Conditioning - Shelke, S. T.; Tibile, R. M.; Belsare, S. S.; Pawase, A. S.; Ghode, G. S.; Pawar, R. A.; Yadav, S. R. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted from August–September, 2024 at the Fish Seed Production Center and Fish Farm of the College of Fisheries Science, Nagpur, Maharashtra, India to systematically evaluate metabolic and stress-related responses of Labeo catla fingerlings under varying stocking densities to determine and standardize the optimal conditioning density that minimizes stress, reduces mortality, and enhances post-transport efficiency. In this study, Catla fingerlings (90.82±5.91 mm) were conditioned in a flow-through system with a water exchange rate of 6.5 l min-1 for the period of 24 h, during this, fingerlings were stocked at four densities: 1 fingerling l-1, 2 fingerlings l-1, 3 fingerlings l-1, and 4 fingerlings l-1. During conditioning, blood samples were collected for glucose, lactate, hemoglobin, and hematocrit estimation, while muscle samples were used for glycogen analysis following anesthesia with clove oil and humane euthanasia. Water quality parameters such as dissolved oxygen and total ammonia nitrogen were monitored to assess metabolic load under varying densities. The results showed density-dependent stress responses. 4 fingerlings l-1 exhibited significantly higher blood glucose and lactate, lower glycogen levels, and greater mortality (p<0.05), indicating elevated stress. While water quality remained stable overall, 4 fingerlings l-1 showed more DO depletion and total ammonia buildup. 3 fingerlings l-1 showed the best balance between stocking pressure and physiological stability, indicating it was the optimal conditioning density for Catla fingerlings in flow-through systems.